2015
DOI: 10.1111/hsc.12264
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with social care: the experiences of people from Chinese backgrounds with physical disabilities

Abstract: What is known about this topic• Underutilisation of disability support services is common among people from Chinese backgrounds in England.• A lack of knowledge of services available and language difference are known factors that lead to underutilisation.• In traditional Chinese societies, family bears the main responsibility for looking after relatives with health and social care need. What this paper adds• Language difference creates a barrier to negotiating access to and navigating through social care.• The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This could be because the participants had less awareness of the social care services available in England. This is consistent with Yeung et al’s (2016) study which showed that only a small number of Chinese people had access to social care in England. The fact that participants had low awareness of social services could also be why they had a feeling of being marginalized.…”
Section: Aimsupporting
confidence: 92%
“…This could be because the participants had less awareness of the social care services available in England. This is consistent with Yeung et al’s (2016) study which showed that only a small number of Chinese people had access to social care in England. The fact that participants had low awareness of social services could also be why they had a feeling of being marginalized.…”
Section: Aimsupporting
confidence: 92%
“…Results presented from the perspective of PWD [35,64,67,68,75] and close others [67,70] suggested a preference for DSWs taking a person-centred, humanistic approach to support. Feeling "seen" as a person was described by multiple participants with disability [35,67,75]. For example, a participant with multiple sclerosis expressed feeling understood and seen as a person when her support worker made individualised suggestions around her care [67].…”
Section: Individualised Supportmentioning
confidence: 97%
“…In line with being responsive to needs, participants with disability valued support sensitive to their specific language and cultural needs [67,75]. The explicit focus of Yeung et al's [75] study was the experiences of Chinese PWD living in the UK and all participants appreciated support that met their language and cultural needs, or were Chinese-specific. This preference extended across all welfare services.…”
Section: Individualised Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest is spread thinly across the country with clusters living in major cities such as Birmingham (12,700), Liverpool (7,978) and Manchester (13,500). The wide geographical distribution means that many might struggle to get help from culturally equivalent support networks in time of need (Yeung, Partridge, & Irvine, ; Rochelle & Shardlow, ). This raises the question of where and to whom they will seek help for MHPs.…”
Section: Introductionmentioning
confidence: 99%